IDENTIFICATION OF MOSS PLANTS AROUND NAMORAMBE DISTRICT - Dinda, Cindy Silvia; Wulandari, Riris; Fachrizal, Ahmad; Ulfa, Syarifah Widya (ISER (Indonesian Science Education Research), 2024)
Non-vascular plants, such as mosses (Bryophyta), are commonly found on land. The class of plants known as tuberous plants, or plants that do not have true roots, stems, or leaves as well as xylem and phloem vessels, includes moss plants. Knowing the diversity of moss plants in Namorambe Sub-district is the purpose of this research. On May 9, 2024, this research was conducted by walking around the Namorambe area to look for moss plants that might be there. This research methodology is qualitative, using descriptive and exploratory techniques. This research used observation, documentation, and literature study as data collection methods. Direct investigation into the Namorambe area was used to make observations to identify moss plants. The three species identified based on the results of the identification of leaf mosses around Namorambe Sub-district were Hyophila sp., Pogonatum cirrhatum, and Barbula indica. Leaf mosses were made near people's work areas and were made on tree bark and stone substrates